Carbon Emissions and Redistribution: The Design of Carbon Tax Rebates - Lea Fricke; Clemens Fuest; Dominik Sachs (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We study optimal redistribution and carbon taxation in a Mirrlees framework. Households differ in their carbon footprint due to both (i) the overall level of spending and (ii) the composition of spending. Introducing a cap on carbon emissions reduces the social value of output, which lowers the efficiency costs of taxation and thereby strengthens the scope for redistribution. However, the optimal increase in redistribution is weaker than suggested by popular proposals for a carbon dividend. While the optimal rebate schedule overcompensates low-income households and undercompensates high-income households for their carbon tax burden, the rebate nevertheless rises with income. Quantifying the model for Germany, we find that the optimal rebate for the 90th income percentile is nearly three times that for the 10th percentile, whereas carbon tax payments are about seven times higher. This results in higher effective average tax rates at the top and lower ones at the bottom of the income distribution.
Keywords: H21; H23; Q58; 330; carbon tax; optimal taxation; carbon dividend